2023
DOI: 10.1002/epi4.12751
|View full text |Cite
|
Sign up to set email alerts
|

RARS1‐related developmental and epileptic encephalopathy

Abstract: ObjectiveBiallelic variants of RARS1, a gene that encodes the cytoplasmic tRNA synthetase for arginine (ArgRS), are associated with central nervous system (CNS) manifestations, such as hypomyelinating leukodystrophy‐9 and developmental and epileptic encephalopathy (DEE). This study aimed to better understand the RARS1 biallelic mutations and the associated phenotypes, particularly in patients with DEE.MethodsWe identified two patients with RARS1 biallelic mutations and functionally validated these mutations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…We identified that RARS1 homozygous variants can cause a variety of neurological symptoms, which is consistent with earlier findings (Di Bella et al., 2021 ; Ji et al., 2018 ; McSherry et al., 2018 ; Mendes et al., 2020 ; Nafisinia et al., 2017 ; Rezaei et al., 2019 ; Wan et al., 2023 ; Wolf et al., 2014 ). In the prior study, the clinical presentation was divided into three categories: severe, intermediate, and mild.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We identified that RARS1 homozygous variants can cause a variety of neurological symptoms, which is consistent with earlier findings (Di Bella et al., 2021 ; Ji et al., 2018 ; McSherry et al., 2018 ; Mendes et al., 2020 ; Nafisinia et al., 2017 ; Rezaei et al., 2019 ; Wan et al., 2023 ; Wolf et al., 2014 ). In the prior study, the clinical presentation was divided into three categories: severe, intermediate, and mild.…”
Section: Discussionsupporting
confidence: 92%
“…Variants in the genes encoding cytoplasmic and mitochondrial tRNA synthetases have been associated with a variety of disorders, ranging from peripheral neuropathy to leukodystrophy (Wolf et al., 2014 ). Biallelic RARS1 variants have been linked to hypomyelination leukodystrophy in 30 cases (Di Bella et al., 2021 ; Ji et al., 2018 ; McSherry et al., 2018 ; Mendes et al., 2020 ; Nafisinia et al., 2017 ; Rezaei et al., 2019 ; Wan et al., 2023 ; Wolf et al., 2014 ). In this study, we used ES on 2 Iranian patients, both had Bakhtiari ethnicity and a history of consanguineous marriage.…”
Section: Discussionmentioning
confidence: 99%